Różewicz o sobie samym jako innym - Przybylski, Ryszard Kazimierz (Przestrzenie Teorii, 2014)
It seems that Tadeusz Różewicz’s poem titled Francis Bacon or Diego Velazquez in a Dentist’s Chair is dedicated to the works of the author of Studies of Crucifixion. In fact, Różewicz writes about the impression that Bacon’s art left on him when he saw it in galleries and museums. This poem is also about fascination. Contrary to what may seem intuitive, it is not an attempt to describe the poet’s own way of interpreting these works; and even if so, this is only true to a limited extent. For Różewicz, Bacon’s works were just a pretext to look at himself, especially at his own early poems, from a distance – from a somewhat ironic distance. In this way the poet is able to present himself as “the other”, thus referring to the title of Paul Ricoeur’s book.